Effect of pH on the kinetics of soybean lipoxygenase‐1 - Asbi, B. Ali; Wei, L.S.; Steinberg, M.P. (Wiley Blackwell, 1989)
The influence of pH on the kinetics of soybean lipoxygenase‐1 was examined. Lipoxygenase‐1 was stable when preincubated in the pH range from 3.2 to 9.2 but was irreversibly denatured at pH 3.0 and below. Double reciprocal plots for undenatured enzyme in the pH range 5.6 to 9.2 showed that the enzyme obeyed Michaelis‐Menten kinetics in this pH range. The Dixon plot (log Vmax/Km vs pH) indicated an active site of the free enzyme to be a histidine residue with a pK of about 7.3.